Vleuelkleppe in die outomatiese verdeling van besproeiingswater. - Van Niekerk, Petrus Hendrik (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M.Ing.) -- Universiteit van Stellenbosch, 1973.